Effects of the pneumoperitoneum in rats submitted to a unilateral nephrectomy: morphologic and functional study on the remnant kidney - Santos,Luiz Sergio (2005)
PURPOSE: The aim of this experimental study is to analyze the morphologic and functional effects of the pneumoperitoneum on the remnant kidney in rats submitted to a unilateral nephrectomy. METHODS: Forty-eight male adults Wistar rats , with an average weight between 240 to 350 g, were distributed in three groups. The rats in Group 1 were subdivided into two other subgroups: Control Group 1A and 1B. Groups 2 and 3 and respective subgroups included 12 rats each. All animals were anesthetized and submitted to a puncture. Animals in Groups 2 and 3 were submitted to abdominal insufflation with CO2, during 2 and 4 hours respectively, with a constant IAP of 15 mmHg. Rats of the Control Group 1A and 1B were maintained punctured during 2 and 4 hours respectively, however, without insufflation. In the end of this period, a left nephrectomy was performed in all animals. After 4 weeks, a new pneumoperitoneum with the same duration was installed, according to the groups. After 8 weeks, the animals were submitted to euthanasia to remove the remnant kidney. Samples of blood were collected during the whole experiment to evaluated the renal function by dosing serum creatinine. The remnant kidney was analyzed microscopically to evaluate its level of glomerular hypertrophy, the number of mesangial cells, and to observe the presence of glomerular sclerosis. All groups were kept under observation and the results were submitted to statistical analysis by a longitudinal and transversal comparative study. RESULTS: At the evaluation of residual renal function no significant clinical alteration was seen in rats submitted to pneumoperitoneum during 2 and 4 hours after a period of 8 weeks. The morphologic analysis of the remnant kidney showed no histological renal injury in the groups. CONCLUSION: The function and renal morphology of rats submitted to a unilateral nephrectomy were not significantly influenced by prolonged and successive pneumoperitoneum, according to this study's biochemical and histological findings.